PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, BUDAYA SEKOLAH, DAN PELATIHAN TERHADAP KINERJA GURU PADA SEKOLAH SWASTA DI KOTA CILEGON - Sueb, Muhamad; Naufal Affandi; Umalihayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to reveal how much influence the principal's leadership style, school culture and training have on teacher performance in Cilegon Private Middle Schools. Using quantitative methods, this research involved 200 teachers as a sample from a total of 386 teachers in the city.The results of the analysis show that the principal's leadership style and school culture together have a significant influence on teacher performance. The combination of these two factors is able to explain 40.7% of the variation in teacher performance. This means that there are still other factors that have not been examined in this research which also influence teacher performance by 59.3%. Further analysis shows that when the training variable is added in the model, all three variables (leadership, culture, and training) significantly influence teacher performance. This indicates that training also plays an important role in improving teacher performance, in addition to leadership style and school culture.